The role of ultrasound-treated sludge for accelerating quinoline mono-oxygenation. (1st March 2019) - Zhang, Yuting; Wang, Youke; Lu, Qinyuan; Zhang, Chenyuan; Yan, Ning; Zhang, Yongming; Rittmann, Bruce E.
Abstract: Activated sludge treated by ultrasound was tested as a source of exogenous electron donor to accelerate quinoline mono-oxygenation, which requires an intracellular electron donor (2H). The quinoline-removal rate was proportional to the amount of treated or untreated sludge added in flask experiments, but the best biodegradation kinetics was obtained with a mixture of 25% untreated sludge plus 75% treated sludge. The treated sludge primarily provided exogenous electron donor, while the untreated sludge provided active biomass. A biofilm system also showed the same beneficial effect of treated sludge, and the soluble fraction of the treated sludge had the greatest impact. Using treated sludge instead of a purchased electron donor provides an economic advantage for accelerating the biodegradation of contaminants whose biodegradation is initiated by an oxygenation reaction, such as quinoline. Graphical abstract: Image 109183 Highlights: Sludge treated by ultrasound provided electrons to accelerate quinoline mono-oxygenation. Combining untreated and treated sludge gave faster kinetics than either alone. Untreated sludge replaced biomass inactivated by ultrasound. Soluble components from treated sludge were more potent donors than the biomass solids.